FACTORS INFLUENCING THE DEVELOPMENT OF ENGLISH SPEECH - Kabulova Zulfiya Xojabayevna (Modern American Journals, 2025)
This study examines the key factors influencing the development of oral communication skills in English within higher education institutions. It highlights the significance of psychological aspects such as self-confidence and foreign language anxiety, as well as the role of personal interest, motivation, and supportive classroom environments in enhancing student participation. Furthermore, the analysis underscores the importance of methodological approaches, including communicative and formative assessment, which encourage learners to engage in authentic communication and allow them to identify and address their weaknesses. The findings suggest that the development of oral speech in English is a complex and multifaceted process shaped by psychological, motivational, methodological, and organizational factors. A comprehensive understanding and conscious integration of these factors into the educational process can effectively foster students’ ability to communicate fluently and confidently in English.
Keywords: Physiological mechanism, foreign language anxiety, industrialization, constructive